Examples and Rules in Mastering a Skill - Beran, Ondřej (Organon F, 2015)
Wittgenstein describes the process of mastering a rule (adopting a skill) as implanting mechanically a number of specific examples (steps) after which one “knows how to go on”. Such a two-step concept of learning (e.g. in Cavell) can be understood as the sequence of i) propedeutics limited in time and ii) the subsequent skill to extrapolate the rule in unlimited number of cases (Chomsky’s account of rule). The relationship between the “propedeutics of examples” and the mastered skill is, however, more complex. I will refer here to the Wittgensteinian ethics (e.g., Winch) emphasizing the individual’s repeated work (reflection) on specific examples which never ends. I will also point to the empirical evidence (Ingold, in particular) that in the processes of learning an essential role is played by memorizing and copying of given (specific) models, where attention and observation is necessary. Competence is then a physical implantation and individual mastering of such a limited technique, rather than an ability to extrapolate and innovate foremost.
Keywords: Examples; extrapolation; perspective; rules; situatedness